2017
DOI: 10.1080/10803548.2016.1274159
|View full text |Cite
|
Sign up to set email alerts
|

Determining the level and cost of sickness presenteeism among hospital staff in Turkey

Abstract: The problem of sickness presenteeism is mostly observed in women and nurses. It causes both financial burdens and productivity losses for hospitals. These survey results are thus expected to provide critically important information on presenteeism for decision-makers and healthcare managers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 34 publications
2
43
0
7
Order By: Relevance
“…The high prevalence of presenteeism found among care assistants is in line with findings from studies from other countries [3][4][5][6]11,20,[27][28][29]. Unlike the present study, other studies have found that nursing professionals have higher levels of presenteeism than other occupations [7,9,16,17,30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The high prevalence of presenteeism found among care assistants is in line with findings from studies from other countries [3][4][5][6]11,20,[27][28][29]. Unlike the present study, other studies have found that nursing professionals have higher levels of presenteeism than other occupations [7,9,16,17,30].…”
Section: Discussionsupporting
confidence: 90%
“…A higher incidence of presenteeism among nurses may therefore lead to more negative health consequences, which in the long run could result in negative consequences for health organisations and patients [14]. Working while ill may result in low work ability, inefficient work, and an increase in errors, which may lead to productivity loss and, in the case of healthcare personnel, to lower medical safety for patients [15][16][17]. The costs of presenteeism have been examined in different healthcare contexts, with the findings indicating that presenteeism can adversely affect the quality of patient care and negatively affect patient safety [18], worsen the spread of infectious diseases [19], and delay patient healing [1].…”
Section: Introductionmentioning
confidence: 99%
“…The nursing sector has been extensively studied in relation to role overload, high pressure at work, relationships with supervisors and mental health conditions (Perry et al 2015;Schneider et al 2017;Skela-Savic et al 2017). Several studies have also demonstrated how productive decreases in nursing attendance while presenteeism occurs (Aysun & Bayram 2017;Noben et al 2015Noben et al , 2014Umann et al 2014). In Spain, there are studies that reveal the need to continue investigating presenteeism as a phenomenon that has negative repercussions for the company, the employee and the quality of patient care, as well as being considered a predictor of future diseases and absenteeism, and can therefore lead to the establishment of prevention and occupational health policies for professionals (S anchez-Zaballos et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Presenteeism refers to the inability to focus at work, efficiency/impaired performance at work, or choosing to go to work instead of resting at home (Aysun & Bayram, ). The causes may be job‐related (job insecurity, fear of losing income, downsizing, work overload, understaffing, overtime, employee‐employer relations, and burnout) (Canada, H. C. o., ; Collins & Cartwright, ; Gilbreath & Karimi, ; Higgins, Duxbury, & Lyons, ; Quazi, ) or based on personal characteristics (gender, age, occupation, and number of children) (Aysun & Bayram, ; Weyman, Meadows, & Buckingham, ). Sickness presenteeism (SP) is a phenomenon in people who attend work despite being sick or feeling like they should have taken sick leave (Aronsson, Gustafsson, & Dallner, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight that both behaviours impact the work organization by decreasing work productivity (absenteeism means no work productivity, and presenteeism yields lower than expected productivity), which raise costs (Kivimäki et al, 2003;Rantanen & Tuominen, 2011;Schultz & Edington, 2007). Sickness presenteeism is often a hidden cost because workers are physically present but unable to perform at peak levels due to a health condition (Aysun & Bayram, 2017;d'Errico et al, 2016;Hemp, 2004). The financial impact of sickness absenteeism was analysed in numerous studies.…”
mentioning
confidence: 99%